VERIFICATION OF QUANTITATIVE ANALYTICAL METHODS IN MEDICAL LABORATORIES - Abdel Ghafar, Muhammad T.; El-Masry, Muhammad I. (Journal of Medical Biochemistry, 2020)
Background: Globally, all medical laboratories seeking accreditation should meet international quality standards to perform certain specific tests. Quality management program provides disciplines targeted to ensure that quality standards have been implemented by a laboratory in order to generate correct results. The hallmark of the accreditation process is method verification and quality assurance. Before introducing a new method in your laboratory, it is important to assess certain performance characteristics that reflect the concept of method verification. Methods: In this review, we illustrated how to verify the performance characteristics of a new method according to the recent guidelines. It includes an assessment of precision, trueness, analytical sensitivity, detection limits, analytical specificity, interference, measuring range, linearity, and measurement uncertainty. Conclusions: Although the presence of several updated guidelines used to determine the performance characteristics of new methods in clinical chemistry laboratories, the real practice raised several concerns with the application of these guidelines which in need for further consideration in the upcoming updates of these guidelines.